Identification of Aleutian mink disease parvovirus transcripts in macrophages of infected adult mink. - Kanno, H (1992)
We examined Aleutian mink disease parvovirus (ADV) mRNA expression in lymph nodes of adult mink infected with ADV by Northern (RNA) blot and in situ hybridization. In Northern blot analysis, ADV transcripts were detected in the poly(A) RNA fraction extracted from mesenteric lymph nodes of two of five mink 10 days after intraperitoneal inoculation with the virulent Utah I strain of ADV. In strand-specific in situ hybridization, ADV DNA and mRNA were detected in some macrophagelike cells located in the medullary sinus in mesenteric lymph node sections from two of six infected mink by using biotinylated probes. In suspensions of lymph node cells, about 30% of the cells phagocytic for latex particles contained ADV DNA and about 1% of these cells contained ADV mRNA. In peritoneal exudate cells, about 20% of the macrophagelike cells contained ADV DNA and about 2% of these cells contained ADV mRNA. These results indicated that some macrophages in ADV-infected mink contained ADV mRNA and were target cells in ADV infection.